TWO LANDMARK PROCEDURE OF SYNTHESIS OF SYSTEMS OF QUASIORTHOGONAL SIGNALS FOR CHANNELS WITH VARIABLE PARAMETERS - Dmitry Viktorovich Gaychuk; Veronica Yurievna Gaychuk (Вестник Северо-Кавказского федерального университета, 2022)
In this article the technique of synthesis of ensembles of discrete quasiorthogonal signals for the mixed system of consolidation allowing significantly to increase speed of information exchange in incoher- ent channels with an intersymbolical interference is offered.